Maternal F1 antibodies and cytokines in mother-neonate dog pairs in the Marmota himalayana plague focus - Deming Tang; Asaiti Bukai; Shuai Qin; Ran Duan; Dongyue Lyu; Zhaokai He; Xiaojin Zheng; Weiwei Wu; Junrong Liang; Haifu Qu; Aidai Bieke; Peng Zhang; et al. (Heliyon)
In this study, we investigated the F1 antibody against Yersinia pestis in the sera of mother-neonate shepherd dog pairs in the Marmota himalayana plague focus of the Altun-Qilian Mountains, Qinghai-Tibetan Plateau, China. Seropositive shepherd dogs lived in plague-endemic regions, where marmots were infected with Y. pestis, whereas seronegative dogs lived in non-endemic regions. The neonatal F1 antibody titers positively correlated with the maternal titers within 3 months after birth, and the neonatal titers were similar to or slightly lower than the maternal titers. In the absence of reinfection, antibodies in the neonates were obtained from their mothers; titers decreased with age and disappeared after 3 months. Mean tumor necrosis factor (TNF)-α, interleukin (IL)-6, IL-2, IL-10, and nerve growth factor (NGF)-β were higher in the mothers than in neonates. Maternal TNF-α, IL-10, vascular endothelial growth factor (VEGF)-A, and NGF-β and neonatal monocyte chemoattractant factor (MCP)-1 and VEGF-A were positively correlated with F1 antibody titers. Our results reveal continuing vertical transmission of F1 antibodies between mother dogs and their offspring and cytokine signatures under plague.